On the Construction and Sources of Erwin Panofsky’s Iconology - Lubomír Konečný (Acta Universitatis Carolinae: Philosophica et Historica, 2023)
The article deals with the impact of Karl Borinski and Karl Mannheim on Erwin Panofsky’s iconological method of interpretation of works of visual arts as presented in his 1939 Studies in Iconology. In a slightly different form it was firstly published in The Journal of Medieval and Renaissnce Studies XXXVII, 1974, 368–373.